Interrelation of Subjective and Objective Indicators in Assessing Quality of Life (illustrated by VEB.RF Index) - A. V. Samokhin; S. A. Myasnikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The currenttrendinworkingoutthequalityoflifeindexistheuseofbothobjectiveandsubjectiveindicators. The articlestudiesapproachestoconceptualizationofqualityoflifeandevaluatestheacademicacceptabilityofexisting Russian andinternationalindicesofthequalityoflife. The goalofthepresentarticleistoassesstheinterrelationofobjectiveandsubjectivefiguresinthestructureofqualityoflifeindicesonthebasisof VEB.RF Index. The analysiswascarriedoutbyestimatingthedependenceofthequalityoflifeperceptiononthelevelofeducation, comfortofdwellings, accessibilityofmedicalinstitutionsandfoodstores, contaminationoftheatmosphere, thelevelofprofits, senseofsecurityandhealthindicators (basedondataof 2021). The choiceof VEB.RF Index asananalyticaltoolwasgroundedbythefactthatitsdatabase, incontrasttootherindices, isopenanditsstructureisbasedbothonobjectiveandsubjectiveindicators. The authorsidentifiedthecorrelationbetweenobjectiveandsubjectiveindicatorsanditprovesthenecessitytotakeintoaccountbothtypesofindicatorsforworkingoutthequalityoflife indices.